Recent Advances of 2D Materials in Nonlinear Photonics and Fiber Lasers. Issue 8 (20th February 2020) - Liu, Wenjun; Liu, Mengli; Liu, Ximei; Wang, Xiaoting; Deng, Hui‐Xiong; Lei, Ming; Wei, Zhongming; Wei, Zhiyi
Abstract: The explosive success of graphene opens a new era of ultrathin 2D materials. It has been realized that the van der Waals layered materials with atomic and less atomic thickness can not only exist stably, but also exhibit unique and technically useful properties including small size effect, surface effect, macro quantum tunnel effect, and quantum effect. With the extensive research and revealing of the basic optical properties and new photophysical properties of 2D materials, a series of potential applications in optical devices have been continuously demonstrated and realized, which immediately roused an upsurge of study in the academic circle. Therefore, the application of 2D materials as broadband, efficient, convenient, and versatile saturable absorbers in ultrafast lasers is a potential and promising field. Herein, the main preparation methods of 2D materials are reviewed and technical guidelines for identifying and characterizing layered 2D materials are provided. After investigating the characteristics of 2D materials thoroughly in nonlinear optics, their performances in fiber lasers are comprehensively summarized according to the types of materials. Finally, some developmental challenges, potential prospects, and future research directions are summarized and presented for such promising materials. Abstract : The effects of material thickness on optical nonlinearity are studied as an important subject recently. Here, thickness dependent nonlinear absorption properties of 2D materials in fiber lasers are presented. Those thickness‐dependent photonic devices are successfully applied in fiber lasers to achieve Q ‐switched and mode‐locked operation. Experiments prove that fiber lasers based on those devices have excellent performance in ultrafast optics.